Maltose-neopentyl glycol (MNG) amphiphiles for solubilization, stabilization and crystallization of membrane proteins - Chae, Pil Seok (2010)
The understanding of integral membrane protein (IMP) structure and function is hampered by the difficulty of handling these proteins. Aqueous solubilization, necessary for many types of biophysical analysis, generally requires a detergent to shield the large lipophilic surfaces displayed by native IMPs. Many proteins remain difficult to study owing to a lack of suitable detergents. We introduce a class of amphiphiles, each of which is built around a central quaternary carbon atom derived from neopentyl glycol, with hydrophilic groups derived from maltose. Representatives of this maltose-neopentyl glycol (MNG) amphiphile family display favorable behavior relative to conventional detergents, as tested on multiple membrane protein systems, leading to enhanced structural stability and successful crystallization. MNG amphiphiles are promising tools for membrane protein science because of the ease with which they may be prepared and the facility with which their structures may be varied.